2016
DOI: 10.1158/1078-0432.ccr-15-1432
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor Modulation Optimized for Response (ARMOR) Phase I and II Studies: Galeterone for the Treatment of Castration-Resistant Prostate Cancer

Abstract: Purpose: Galeterone is a selective, multitargeted agent that inhibits CYP17, antagonizes the androgen receptor (AR), and reduces AR expression in prostate cancer cells by causing an increase in AR protein degradation. These open-label phase I and II studies [Androgen Receptor Modulation Optimized for Response-1 (ARMOR1) and ARMOR2 part 1] evaluated the efficacy and safety of galeterone in patients with treatment-naive nonmetastatic or metastatic castration-resistant prostate cancer (CRPC) and established a dos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 33 publications
0
53
0
Order By: Relevance
“…Cerebrovascular disease has high morbidity, death rates and disability rates worldwide, posing a serious threat to public health (14). Approximately 2 million individuals suffer from cerebrovascular disease worldwide and >1.5 million succumb each year (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cerebrovascular disease has high morbidity, death rates and disability rates worldwide, posing a serious threat to public health (14). Approximately 2 million individuals suffer from cerebrovascular disease worldwide and >1.5 million succumb each year (14).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 2 million individuals suffer from cerebrovascular disease worldwide and >1.5 million succumb each year (14). Furthermore, the morbidity is on the increase with improvements in living standards and lifestyle changes (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a phase I study of chemonaive men with CRPC, 22% demonstrated a decrease in PSA of more than 50%, whereas an additional 26% had a PSA decline of 30-50% after 12 weeks. No evidence of adrenal mineralocorticoid excess was noted (Montgomery et al 2016).…”
Section: Cyp17a1 Inhibitorsmentioning
confidence: 97%
“…In the ARMOR3 trial, patients who progress on initial androgen deprivation therapy are screened for the presence of a resistance marker on circulating tumor cells called AR-V7-a truncation of the androgen receptor ligand binding domain at the site where both endogenous androgens and first-and second-generation androgen receptor blockers bind (106,107). The study entails randomizing patients with this resistance marker to either a conventional blocker of the androgen receptor binding domain (enzalutamide) or a drug that acts by binding at a different site in the N terminus of the androgen receptor (galeterone) (108,109). The TAXYNERGY study looks at changing the type of chemotherapy on the basis of earlyresponse markers, including circulating tumor cell number and cellular androgen receptor distribution (110).…”
Section: Smentioning
confidence: 99%